2012
DOI: 10.1007/s00339-012-6813-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective patterning and scribing of Ti thin film on glass substrate by 532 nm picosecond laser

Abstract: In this paper, the feasibility of Ti film coated on glass substrate scribed via a 532 nm picosecond laser is investigated. Laser irradiations from the film side and from the transparent substrate side are performed for comparison. Optical microscopy, SEM, surface stylus and contact resistance measurement reveal that the Ti film can be completely removed with no damage to the glass substrate, using optimized process parameters. The complete removal threshold for the film for front-side scribing is found at 120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It is normally composed of a non-metallic substrate and a metal film with a special periodic pattern on the substrate, which is mainly processed by laser etching [2][3][4] . Yung studied the laser etching processes of Ti films on Ni-Cu metal/ceramic and glass substrates and found that nondestructive metal film removal can be achieved by adjusting the laser parameters [5] . However, the research was only performed for simple grooves, and no in-depth study on the processing accuracy and efficiency has been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…It is normally composed of a non-metallic substrate and a metal film with a special periodic pattern on the substrate, which is mainly processed by laser etching [2][3][4] . Yung studied the laser etching processes of Ti films on Ni-Cu metal/ceramic and glass substrates and found that nondestructive metal film removal can be achieved by adjusting the laser parameters [5] . However, the research was only performed for simple grooves, and no in-depth study on the processing accuracy and efficiency has been carried out.…”
Section: Introductionmentioning
confidence: 99%